2018
DOI: 10.2196/ijmr.9103
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Entertainment and Communication Devices Among a Saudi Pediatric Population: Cross-Sectional Study

Abstract: BackgroundExcessive use of various electronic entertainment and communication devices, particularly among children, has been associated with increased behavioral problems. Despite children’s escalating use of these devices, parents’ awareness about the impact thereof is still lacking.ObjectiveThe objective of this study was to assess the use of electronic entertainment and communication devices among children attending a health care facility in Jeddah, Saudi Arabia, as well as the parental impression regarding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The aforementioned situation is similar in Saudi Arabia (SA), where the use of communication or electronic entertainment devices is particularly common in the pediatric population (2). Technology usage might impose a negative influence on child's psychosocial development.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned situation is similar in Saudi Arabia (SA), where the use of communication or electronic entertainment devices is particularly common in the pediatric population (2). Technology usage might impose a negative influence on child's psychosocial development.…”
Section: Introductionmentioning
confidence: 99%
“…Extended periods of digital device usage (> 6 h) seem to be a significant risk factor for eye strain in the current study. Other studies from Saudi Arabia reported defined extended duration of digital device usage as more than 4 h and still reported high rates of eye strain [ 12 , 29 31 ]. This relationship between the duration of digital devices usage and eye strain has prompted some experts to suggest a reduction in the number of hours spent in front of computers and other devices to mitigate the risk of serious visual problems [ 20 , 26 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…These screen time guidelines are based on studies that continue to show the association between screen time in early childhood and language delay (Duch et al, 2013;Zimmerman, Christakis, Meltzoff, 2007). However, many Saudi parents lack awareness of screen time restrictions and their impacts on children's development (Amawi et al, 2018). This study aims to describe screen time's impact and its association with language development among preschool-age children in Saudi Arabia.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Previous studies conducted in Saudi Arabia have examined language delay and social factors, including TV exposure in general (AlFadhli & AlBunaian, 2017). Another study examined screen time and behavioral issues for an older age group (8-15 years old) (Amawi et al, 2018). Furthermore, previous studies in other countries have investigated screen time in reference to TV alone.…”
Section: Significance Of the Studymentioning
confidence: 99%